Early involvement and pathway specialization : a dropout track in cross-country skiing? - Więclaw, Grzegorz (2013)
Early sport specialization is often criticized for its potential to impair long-term athletic development. One of the most frequently cited consequences is dropout from further sport participation. Early diversification, within the Developmental Model of Sport Participation (DMSP), postulates that early sampling of various sports and late specialization should result in fewer dropouts. Still, empirical evidence supporting this claim remains scarce. The purpose of this study was to examine dropout rates among Finnish elite youth skiers in relationship to: (a) their developmental pathways, (b) age of first involvement with organized cross-country skiing, and (c) first encounter with organized sport. This study adopted a retrospective follow-up design. The sample consisted of 152 skiers who raced competitively in the 2009/2010 season. Data concerning demographics and sport history was collected through a postal self-report questionnaire. The participation status of skiers was followed-up three years later from the Finnish Ski Association’s data base. Twenty-eight distinct developmental pathways were identified and assigned into specialized (n = 7) and non-specialized pathway (n = 21) categories. Based on the data distribution for age of first involvement, skiers were grouped into three categories: early (2-5 years), normal (6-8 years) and late (9-13 years). The mean age was 7.41 years (SD = 2.51). Eighty skiers (52.6%) in the sample indicated a cross-country skiing club to be their first ever encounter with organized sports, while the remaining 72 (47.4%) practiced other sports before engaging with organized cross-country skiing. The results of chi-square tests found no statistically significant association between dropout and the three variables (pathway category, age of first involvement, first organized sport experience). Only the comparison between normal and late involvement groups showed a significant difference between the groups, suggesting an association between late involvement and dropout. Thus, earlier involved skiers were less likely to drop out than skiers who started relatively late. The results of the study are discussed within the DMSP framework. In general, they provide no clear support for the early diversification hypothesis; rather they suggest an optimal age window for first involvement in cross-country skiing and gradual specialization.